The Effect of the Unting Debt Game (Anti-Stunting Snake and Ladder) on Increasing Knowledge About Stunting - Lestari, Cahaya Indah; Pamungkas, Catur Esty; WD, Siti Mardiyah; Amilia, Rizkia; Adiputri, Ni Wayan Ari; Rospia, Evi Diliana; Makmun, Indriyani; Amini, Aulia; Cahyaningtyas, Dwi Kartika (EMBRIO: Jurnal Kebidanan, 2024)
The prevalence of stunting in the world, as collected by WHO in 2020, was 150.8 million (22.2percent). WHO has designated five regions as stunting prevalence, including Indonesia in the Southeast Asian region with a prevalence rate (36.4percent). Adolescents are a group that has the potential to be agents of behavior change. For this reason, adolescents need to be given education to increase knowledge and build awareness of the impact of stunting in the future. This study aims to determine the influence of Uting Debt Media (Snake and Ladder Stunting) in increasing adolescents' knowledge about stunting. This research is quantitative. The type of research used was Quasy Experimental pretest and posttest with the control group. The population in this study is all young women of MTS Jamaluddin Bagik Nyaka Village in August 2024, with a sample of 30 people divided into two groups with 15 members each and using purposive sampling techniques. Data collection was carried out using a questionnaire to determine the level of knowledge of adolescent girls about stunting before and after the intervention. The statistical results of the post-test of the experimental and control groups using the Mann-Whitney techniques showed Asymp. signature. (2-tailed) 0.012 less than 0.050, with the mean rank of the experimental group of 19.00 and the mean rank of the control group of 12.00. So, it can be concluded that there is a significant difference in the results of the post-test of the experimental group and the control group, which affects the increase of knowledge in the experimental group before and after being given treatment to increase adolescent knowledge about stunting